CORROSION BEHAVIOR OF POWDER METALLURGY ALUMINUM ALLOY 6061/AL2O3 METAL MATRIX COMPOSITES - Gasem, Zuhair M. (2020)
The electrochemical behavior of aluminum alloy 6061/Al2O3 metal matrix composite was investigated in 3.5% NaCl aqueous solution. Two composite compositions were examined containing 10% and 30% (by volume) of sub-micron alumina particulates as the reinforcement phase. The composites were fabricated via powder metallurgy processing. Cyclic polarization tests were carried out to determine pitting potentials and repassivation potentials in deaerated 3.5% NaCl solution. The pitting potential was 50 mV more noble for the higher-content reinforcement composite, while the repassivation potentials were essentially identical. The scanning electron microscope was used to reveal pits morphologies generated potentiostatically at a potential 150 mV more noble than the open circuit potentials for two hours immersion in quiescent chloride solution. Excessive pitting of the matrix alloy was observed in both composites. Pits forming in the 6061/Al2O3/30p composite were more numerous and more uniformly dispersed compared to pits on the lower-content reinforcement composite which were deeper and more localized. Preliminary results suggest that pit initiation sites correlate with regions exhibiting agglomeration of the reinforcement particles.